ORGANIZATIONAL AND LEGAL MODEL OF ACTIVITY OF SUPERVISORY BODIES OF EMERCOM OF RUSSIA AIMED AT PREVENTION OF VIOLATION OF MANDATORY REQUIREMENTS - Olga D. Ratnikova; Pavel P. Kononko; Dmitry N. Kurkin; Nadezhda M. Illarionova (Актуальные вопросы пожарной безопасности, 2020)
The analysis of normative legal acts in the field of activities of supervisory bodies of EMERCOM of Russia, as well as the analysis of activities of supervisory bodies of EMERCOM of Russia in the field of violation of fire safety mandatory requirements is carried out. There is proposed the organizational and legal model of operation of supervisory bodies of EMERCOM of Russia aimed at prevention of violation of mandatory requirements based on aforesaid analysis. The model includes a set of elements primarily associated with the necessity to amend several normative legal acts.